Toksisitas Ekstrak Etanol Mangifera foetida L. Sebagai Pengkelat Besi Ditinjau dari LD50 dan Komponen Sel Darah - Tri Wahyuni; Santi Purna Sari; Ari Estuningtyas; HJ Freisleben (Universitas Indonesia, 2015)
Ethanolic extract of bacang mango leaves (Mangifera foetida L.) was reported could decrease blood iron concentration of iron overloaded-Sprague dawley rats. The aim of this experiment was to determine acute toxicity (LD50) value of ethanolic extract of M. foetida by weil method and its effect to blood component. This study was conducted by employing a complete random design using 25 male and 25 female mice of DDY strain which was divided into 5 groups. The first until fourth group were administered by the aquadest suspension of ethanolic extract of M. foetida with dose variation, orally. The fifth group was control group that administered by aquadest only. The LD50 was determined by the total of death on all group. LD50 value of the extract showed no death in the biggest doses (13.013 g/kg). The examination was continued with measured blood count (erythrocytes, trombocytes, leukocytes, and haemoglobin concentration). It was shown that the extract at dose 1.626; 3.253; 6.506 and 13.013 g/kg unchanged the blood count measurement. It is concluded that Mangifera foetida L. leaf was not toxic, but could not change the blood count measurement.